Pacific Islands - Regional Economic Report : Embarking on a Global Voyage - Trade Liberalization and Complementary Reforms in the Pacific - World Bank (Washington, DC, 2013)
This regional economic report, evaluates the strategy that the Pacific Island Countries (PICs) have chosen towards liberalizing their economies, and, analyzes as well the interaction of trade liberalization with complementary reforms in taxation, and the public sector. As a consequence of multilateral and unilateral efforts towards freer trade worldwide, preferential access granted to PICs in developed country markets, is being eroded. In particular, the report looks at the Pacific Island Countries Trade Agreement (PICTA), viewed as a "stepping stone" to become more competitive in global markets. It is important to note that the formation of a preferential trade area, as opposed to multilateral or unilateral liberalization, is perceived as trade liberalization, but in a gradual process, to limit disruptions, and adjustments to their economies. However, in order for this "stepping stone" not to become a "stumbling block," the liberalization strategy needs to be actively pursued, through sound policy framework, and trade facilitation. Furthermore, the small un-diversified economies of, and very little trade among PICs suggests very small benefits from PICTA; yet, trade diversion which favors the more industrially advanced members is likely to develop. Nonetheless, the formulation of a free trade agreement between the PICs, and Australia and New Zealand, negotiations over reciprocal free trade agreements with the European Union in 2002 as envisaged, and provision of a free trade association by some PICs with the United States, inevitably will require the widening of preferential trading arrangements beyond PICTA, though the timing is uncertain. It is suggested that the pace and composition of reforms - in particular, more complete trade liberalization, and public sector reform - will need to be calibrated to the progress on efforts to enhance the business environment, and increase labor, and capital mobility.